Mutualism and health care : Hospital contributory schemes in twentieth-century Britain. - Gorsky, Martin; Mohan, John.; Willis, Tim. (Manchester : Manchester University Press, 2006)
Mutualism and health care presents the first comprehensive account of a major innovation in hospital funding before the NHS. The voluntary hospitals, which provided the bulk of Britain?s acute hospital services, diversified their financial base by establishing hospital contributory schemes. Through these, working people subscribed small, regular amounts to their local hospitals, in return for which they were eligible for free hospital care. Mutualism and health care evaluates the extent to which the schemes were successful in achieving comprehensive coverage of the population, funding hospital.
Chapter 9'Where the shoe pinches': reorientation under the National Health Service; Chapter 10; The health cash plans and the new mutualism in health care; Chapter 11; Concluding comments; Index; Acknowledgements; Abbreviations.
Print version record.
Includes bibliographical references and index.
English.
JSTOR
Keywords: National health services -- Great Britain; Mutualism; Hospitals -- Administration; Hospitals -- Business management; Health services administration; Economics; Organization; Health facilities; History; Medical care; Humanities; Hospital Administration; Financial Management; Health Care Quality, Access, and Evaluation; Patient Care Management; History, Modern 1601-; Economics; Health Care Economics and Organizations; Organization and Administration; Health Facilities; Health Services Administration; History; Delivery of Health Care; Health Care Facilities, Manpower, and Services; Humanities; Economics, Hospital; Financial Management, Hospital; Financial Support; History, 20th Century; Patient Care Management -- methods; History, Early Modern 1451-1600; Patient Care; Services de santé -- Grande-Bretagne.; Mutualisme (Économie politique); Hôpitaux -- Administration; Services de santé -- Administration; Médecine -- Histoire -- 1500-; Économie politique; Organisation; Équipements sanitaires; Histoire; Prestation de soins; Sciences humaines; Hôpitaux -- Aspect économique.; Médecine -- Histoire -- 20e siècle.; Soins médicaux.; economics; health facilities; history (discipline); humanities; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; POLITICAL SCIENCE -- Comparative Politics; Organization; Medical care; Humanities; Hospitals -- Business management; Hospitals -- Administration; History; Health services administration